Application of models of the requirements of comprehensive quality management for the study of sports education for pupils of special education - AHMED IQAAB AL-HCSENAWEY, SHIHAB; AudaikairamRhman (International Journal of Psychosocial Rehabilitation, 2020)
The research addressed the issue of slow students learning as part of human energy, which must be well invested and take their hands from slow learning and reduce as much as possible differences between them and the institutions concerned, they had to find methods of thought and suspense of education in order to reach and raise this category for the better in line with what the educational process requires and the problem of research has crystallized in wondering whether there are applied measures to manage the overall quality of students slow learning and what applications of the procedures adopted for the management of the school. Therefore, the research sample, which included (10) schools distributed in Diyala province and its teachers and pupils, the researchers reached conclusions, the most important of which is the lack of application of comprehensive quality management procedures for students as well as the procedural applications adopted to manage the schools concerned and directed the researchers to recommendations, the most important of which is the qualification of the staff for special education classes and the dissemination of a culture of overall quality as well as a review of the curricula of special education classes and learning methods, as well as work to activate the special education unit and work to consolidate the concept of comprehensive quality requirements in the continuous work in the school.